Representation of behavioural world image in verbal lexis - Almira Askhatovna Aminova, Alsou Mirzayanovna Aydarova, (Opción, 2019)
The purpose of the article is to show how the lexis of the language reveals the behavioral prohibitions, norms and imperatives existing in this linguistic community via the method of component analysis and the comparative method. The results of the study show that the cultural information about the norms and prohibitions of behavior which contain in the semantics of verbal units construct to some extent a fragment of the behavioral world image. In conclusion, the cultural component stored in lexical units with the meaning of behavior is to some extent constructed fragments of a behavioral image of the world.